2015
DOI: 10.1039/c5ay00502g
|View full text |Cite
|
Sign up to set email alerts
|

Investigating optimum sample preparation for infrared spectroscopic serum diagnostics

Abstract: Biofluids, such as serum and plasma, represent an ideal medium for disease diagnosis due to their non-invasive character, ease of collection, that can be performed worldwide, and their fundamental involvement in human functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 40 publications
0
46
1
Order By: Relevance
“…Compositions and concentrations vary significantly across the dried droplet, due to different molecular weights and relative molecular solubilities, and can cause band saturation in transmission FTIR [26] but Raman signals are highly reproducible within the ring. Lovergne et al performed an infrared microspectroscopic imaging study on pure, 2 fold, 3 fold and 4 fold diluted serum (serum diluted with deionised water) [141]. The images (Figure 7) highlight the spectral and visible differences between the different sample states.…”
Section: Ex-vivo -Liquid Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compositions and concentrations vary significantly across the dried droplet, due to different molecular weights and relative molecular solubilities, and can cause band saturation in transmission FTIR [26] but Raman signals are highly reproducible within the ring. Lovergne et al performed an infrared microspectroscopic imaging study on pure, 2 fold, 3 fold and 4 fold diluted serum (serum diluted with deionised water) [141]. The images (Figure 7) highlight the spectral and visible differences between the different sample states.…”
Section: Ex-vivo -Liquid Biopsiesmentioning
confidence: 99%
“…Other spectral images were constructed using a single wavenumber. Reproduced from [141] In vitro For in vitro cytological studies, formalin fixation has been demonstrated to best reproduce the characteristics of live cells [147]. Protein coated substrates [148] and 3-D matrices have also been explored to improve measurement protocols [149,150].…”
Section: Ex-vivo -Liquid Biopsiesmentioning
confidence: 99%
“…A study by attenuated total reflectance (ATR)‐FTIR spectroscopy has reported that spectra acquired on pure serum drop cracks suffer from spectral distortions resulting in an abnormal amide I/ II band shape and baseline . Using HT‐FTIR spectroscopy in the transmission mode, we have previously shown the necessity to dilute serum samples to avoid amide bands spectral saturation, providing visually dried drops with greater homogeneity . Moreover, one averaged spectrum is acquired over the whole surface of a silicon plate well.…”
Section: Introductionmentioning
confidence: 99%
“…The volume deposited can have a influence on the data collected, depending on the concentration of the solutions analysed and the coverage of the crystal achieved. The socalled "coffee ring effect" has been documented extensively in literature 53,57 and describes the uneven distribution of the constituents following air drying. Commonly, a higher concentration is obtained on the edge of the deposited material which can result in some spectral variability.…”
Section: Data Pre-processing and Analysismentioning
confidence: 99%